Culture and the Environment: The City Dynamics and Historical Heritage of Akure, Ondo State (2009)
This paper posits that culture and the environment coexist to reflect and accommodate the way of life of a people. The two phenomena like siamese twins are closely knit together. Human development viewed from two categories may be from above or below. The former has its root in the neo-classical economic theory while the latter focuses on the maximum mobilization of each area's natural, human and institutional resources. The paper extensively examines the historical antecedent of Akure as one of the examples of ancient Yoruba cities which have dynamic culture, taboos, identities and historical heritage. It also looks into the parametres that brought dynamic changes to the development of the city in the past fifty years.